Applied autoethnography: A method for reporting best practice in ecological and environmental research. Issue 11 (22nd July 2022) - Murphy, Kilian J.; Griffin, Laura L.; Nolan, Grace; Haigh, Amy; Hochstrasser, Tamara; Ciuti, Simone; Kane, Adam
Abstract: Applied research involves interactions between different organisations—academia, industry, government. Breakdowns in communication can occur during these interactions which alter a project's outcome. We omit how we encounter and overcome these problems from scientific manuscripts which mask the social and cultural considerations that are critical to a project's success. Autoethnography is a form of structured reflection whereby researchers use personal experience to contribute to understanding collaborative processes. We propose an applied form of autoethnography as a repeatable protocol to describe inter‐organisational interactions during the research process in ecology and environmental research. We demonstrate the use of this protocol with five case studies from a diversity of wildlife research across a wide variety of experience levels and scales from small mammals, large herbivores and predators to digital ecology. Our applied autoethnography protocol would ensure that specific biases and context are adequately described and that problems encountered and lessons learned from the experience are reflected upon. These reports can be presented as stand‐alone publications where appropriate, that is, to communicate an effective solution for a novel problem, or within the methods or supplementary material of manuscripts to further explain how the project developed from initial idea to final publication. Furthermore, this protocol can be used by practitioners to evaluate the trajectory of management decisions and policy implications in their jurisdiction to promote transparency and improve communication with stakeholders. Synthesis and Applications : Applied science will continue to intersect with organisations that help or hinder research efforts depending on cultural contexts and biases. Using adequate reflection on case studies to record these experiences and disseminate lessons to the wider community will improve how we approach problems in research, help us to avoid repeating mistakes and ultimately save time and resources. Outside of research, case studies derived from this protocol allow practitioners to holistically understand the methods, biases and challenges of the research from a new perspective, thus providing a novel knowledge brokering function between academia and practitioners in applied ecology. Abstract : Applied science will continue to intersect with organisations that help or hinder research efforts depending on cultural contexts and biases. Using adequate reflection on case studies to record these experiences and disseminate lessons to the wider community will improve how we approach problems in research, help us to avoid repeating mistakes and ultimately save time and resources. Outside of research, case studies derived from this protocol allow practitioners to holistically understand the methods, biases and challenges of the research from a new perspective, thus providing a novel knowledge brokering function between academia and practitioners in applied ecology.